PELATIHAN PEMBUATAN KERAJINAN DAUR ULANG SAMPAH DI BANK SAMPAH SRI REJEKI KELURAHAN BENDA BARU KECAMATAN PAMULANG TANGERANG SELATAN - Irwan Irwan; Mirza Shahreza; Yenni Melia; Tantry Widiyanarti; Hanafi Saputra; Ahmad Hidayah (Indonesian Collaboration Journal of Community Services, 2022)
So far, the waste problem has not been resolved. Environmentally unfriendly behavior, public awareness and participation about waste management is still low. This service aims to conduct training in the manufacture of waste recycling crafts at the Sri Rejeki waste bank, Benda Baru Village, Pamulang sub-district, South Tangerang. The method used in this study started from field observations related to collecting data about communities and society as seen from the spirit of work and concern for the environment and in-depth interviews by conducting discussions with the participants. Then do a direct practice method to make crafts from waste products. Data analysis uses data presentation techniques and conclusions. The results of this service show that participants in the training are more enthusiastic and highly motivated because they get enlightenment about waste recycling. Besides that, participants have a higher level of concern for protecting the environment and obtaining results to be exchanged into use value (money). Participants can gain knowledge about strategies in waste flow from customers as waste management management